Health consideration in food consumption: impacts of education level and custom rules adherence - Sari, Ni Putu Wulan Purnama; Mazenda, Adrino; Tristiana, RR Dian (Intelektual Pustaka Media Utama, 2025)
Individual attributes, such as educational background, may influence the degree of health consideration in food consumption. The local social norms may affect the same consideration in the collective level. Represented by education level and the custom rules adherence in food choosing behavior, this study aimed to examine how knowledge influences health consideration in food consumption and how the local social norms moderate this association in a multicultural enriched society. By utilizing the Bayesian Mindsponge Framework (BMF) as a conceptual framework, this study analyzed a dataset of 710 urban residents in Indonesia. There was a negative association between education level and health consideration in food consumption in which the custom rules adherence in food choosing behavior moderated against this negative association. For those with a low level of custom-based food consumption, their health consideration is lower as they have higher education level. However, the opposite trend which is a more intuitive positive association was found in those who consume more custom-based food. Socio-cultural factors have a complex impact on food choosing behavior among Indonesian urban residents. Therefore, governmental policies in the health promotion campaign of healthy-nutritious food should incorporate socio-cultural aspects with a deeper understanding of the human mind’s information processing.